2022
DOI: 10.3390/agronomy12051071
|View full text |Cite
|
Sign up to set email alerts
|

Field Resistance of Digitaria sanguinalis (L.) Scop. to Haloxyfop-P-methyl in China’s Cotton Fields

Abstract: Large crabgrass, Digitaria sanguinalis (L.) Scop., is a devastating weed species in the cotton (Gossypium spp.) fields in China. It has developed resistance to haloxyfop-P-methyl, an aryloxyphenoxypropionate herbicide known for its ability to inhibit lipid synthesis and induce oxidative stress in weeds, due to years of continuous and intensive use. Here, we present the results from a nation-wide, long-term resistance monitoring effort. To understand the scale and level of haloxyfop-P-methyl resistance, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…GST activity in DsGSTU1 ‐overexpressing rice seedlings was 1.18‐fold the control before haloxyfop‐ P ‐methyl treatment, and 1.40‐, 1.07‐ and 1.15‐fold the control at 36, 72 and 120 h after herbicide treatment, respectively. There was consistently higher GST activity in HR D. sanguinalis plants compared to HS plants 19 . These combined results indicate that DsGSTU1 could contribute to resistance of D. sanguinalis to haloxyfop‐ P ‐methyl.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…GST activity in DsGSTU1 ‐overexpressing rice seedlings was 1.18‐fold the control before haloxyfop‐ P ‐methyl treatment, and 1.40‐, 1.07‐ and 1.15‐fold the control at 36, 72 and 120 h after herbicide treatment, respectively. There was consistently higher GST activity in HR D. sanguinalis plants compared to HS plants 19 . These combined results indicate that DsGSTU1 could contribute to resistance of D. sanguinalis to haloxyfop‐ P ‐methyl.…”
Section: Resultsmentioning
confidence: 71%
“…Our previous work showed that the intrinsic activity of GSTs in HR D. sanguinalis was higher relative to HS plants both with and without haloxyfop‐ P ‐methyl treatment 19 . In this study, to further understand the role of DsGSTU1 in herbicide resistance, a GST activity assay was performed using rice seedlings overexpressing the DsGSTU1 gene.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations